Упростите буквенное выражение:
а) 4(х+5)-2= 4х+20-2х= (-2)х+20= 2х+20


б) 6х-4-2(х-11)
в) 6(х-2) - (3х-12)
г) х - 4-2(3х-12)
д) 5 (3х + 2) - 2( 6х-3)
е) 9( 2х-20) - 6( 3х-30)

2

Ответы и объяснения

2014-02-28T19:00:18+04:00
Б) 6x - 4 - 2(x - 11) = 6x - 4 -2x + 22 = 4x + 18 
в) 6(x - 2) - (3x - 12) = 6x - 12 - 3x + 12 = 3x 
г) x - 4 - 2(3x - 12) = x - 4 - 6x + 24 = 20 - 5x
д) 5(3x + 2) - 2(6x - 3) = 15x + 10 - 12x + 6 = 3x + 16
е) 9(2x - 20) - 6(3x - 30) = 18x - 180 - 18x + 180 = 0 
2014-02-28T19:02:55+04:00
а)  4(х+5)-2= 4х+20-2=4x+18


б) 6х-4-2(х-11)=6x-4-2x+22=4x+18
в) 6(х-2) - (3х-12)=6x-12-3x+12=3x
г) х - 4-2(3х-12)=x-4-6x+24=-5x+20
д)  5 (3х + 2) - 2( 6х-3)=15x+10-12x+6=3x+16
е) 9( 2х-20) - 6( 3х-30
)=18x-180-18x+180=0